2007
DOI: 10.1017/s0305000906007641
|View full text |Cite
|
Sign up to set email alerts
|

Referential communication abilities and Theory of Mind development in preschool children

Abstract: This work aims to analyse the specific contribution of social abilities (here considered as the capacity for attributing knowledge to others) in a particular communicative context. 74 normally developing children (aged 3;4 to 5;9, M=4·6) were given two Theory of Mind (ToM) tasks, which are considered to assess increasing complexity levels of epistemic state attribution: Attribution of knowledge-ignorance (Pillow, 1989; adapted by Welch-Ross, 1997) and Understanding of False-belief (Baron Cohen, Leslie & Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 45 publications
4
30
1
4
Order By: Relevance
“…These results are similar to those found in our study. In addition, the study conducted by Resches and Perez-Pereira (2007) showed significant relationships between false-belief attribution and speaker performance in referential communication, a result that did not appear in our study. The present study, nevertheless, may provide some support for the hypothesis made earlier that there would be a relation between false-belief competence and referential communication ability.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…These results are similar to those found in our study. In addition, the study conducted by Resches and Perez-Pereira (2007) showed significant relationships between false-belief attribution and speaker performance in referential communication, a result that did not appear in our study. The present study, nevertheless, may provide some support for the hypothesis made earlier that there would be a relation between false-belief competence and referential communication ability.…”
Section: Discussioncontrasting
confidence: 89%
“…Additionally, a longitudinal research examining children's performance on tasks assessing ToM competence and referential communication skills would indicate possible age changes, differences, or similarities and, moreover, would provide the basis for an in-depth examination of possible links with other common underpinning factors to both areas of development. A finding that is worth discussing here is the relation between comprehension of ambiguous messages and false-belief understanding also suggested by Resches and Perez-Pereira (2007). This finding together with the reported evidence that comprehension of ambiguous messages is a predictor of false-belief competence provide some basis for the claim that an understanding of ambiguity, the idea that one message might be taken to refer to more than one thing, might go along with a grasp that it is possible to take different perspectives on a thing.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In contrast, errors based on social conformity, may increase with false belief success because, according to some theorists, theory of mind is a prerequisite for social understanding (Astington, 1993), and it is strongly associated with improvements in social communication (Resches & Perez Pereira, 2007;Welch-Ross, 1997). Social conformity occurs when individuals want to appear to be in agreement with others in order to maintain a smooth social interaction to avoid disapproval, even when the other's perspective is privately acknowledged as false.…”
Section: Developmental Factorsmentioning
confidence: 99%
“…La tarea comunicativa que se ha empleado es la comunicativo referencial, en esta tarea se propone que una persona, en el rol de emisor, elabore un mensaje que describa las características de una serie de objetos referentes. Dicho mensaje debe posibilitar que un interlocutor, en el rol de receptor, identifique correctamente dichos objetos (Dickson, 1981;Resches y Pérez-Pereira, 2007). En estas tareas se documenta que la capacidad de elaborar mensajes no ambiguos por parte del emisor (esfera comunicativa pública) está relacionada con la emergencia de elementos de autorregulación de la tarea comunicativa o habla privada (esfera privada).…”
Section: Introductionunclassified